Perspectives of Pediatric Vaccination Among the Batwa Community in Western Uganda: A Qualitative Study - Eustes Kigongo MSc; Marc Sam Opollo PhD; Viola Nalwoga MSc; Marvin Musinguzi MSc; Gad Kwizera MSc; Amir Kabunga PhD (SAGE Publishing, 2024)
Background . Vaccine-preventable diseases contribute significantly to under-five deaths, particularly in low- and middle-income countries. In Uganda, immunization coverage disparities persist among marginalized communities like the Batwa. This study explores perspectives on pediatric vaccination within the Indigenous Batwa in western Uganda. Methods . A qualitative phenomenological approach was used, with data from 15 mothers/caretakers, 8 health extension workers, and 3 community leaders in Kisoro district. Interviews were conducted privately, audio-recorded, and analyzed thematically. Results . Three themes emerged: (1) Misconceptions and concerns about vaccine safety and distrust in Western medicine; (2) Cultural beliefs favoring traditional healing; and (3) Access challenges, including geographical and socioeconomic barriers. Trust and comfort with healthcare providers, especially Batwa, were vital to reducing stigma. Conclusion . Addressing misconceptions, educating on vaccine safety, and building trust are key. Culturally sensitive programs and engaging Batwa care providers can improve vaccine uptake and acceptance by enhancing comfort and trust in vaccination efforts.